Pengembangan Aplikasi Telemedicine Carevul Sebagai Optimalisasi Pelayanan Kesehatan Berbasis Cloud - Ismawati, Nurul; Rosi Subhiyakto, Egia (Infotekmesin, 2024)
Telemedicine is a healthcare service that utilizes information and communication technology to offer virtual medical services, eliminating the need for the physical presence of patients and medical professionals in a single location. The development of telemedicine enhances the accessibility of healthcare services, helps overcome constraints of time and resources, and can reduce healthcare service costs. Consultation services at UPT Puskesmas Tirto Kota Pekalongan are still manual and have not fully optimized the use of technology. The process of meeting the needs for consultations with doctors requires a direct visit to the health center, resulting in a significant use of time and resources. Therefore, a website-based system is needed as a platform to provide easy and practical online telemedicine consultation services. This research employs the prototyping development method, allowing users to participate by evaluating and providing feedback during the development process. System testing using Blackbox and User Acceptance Test (UAT) shows a user satisfaction percentage of 89.6%, indicating that the majority of users strongly agree with the developed website. The development of this website is expected to facilitate users and medical personnel in conducting online consultations anywhere and anytime without the need to visit the health center.